2005
DOI: 10.1002/humu.9329
|View full text |Cite
|
Sign up to set email alerts
|

Biotinidase deficiency: Novel mutations and their biochemical and clinical correlates

Abstract: Biotinidase deficiency is a defect in the recycling of the vitamin biotin. Biotin supplementation can markedly improve the neurological and cutaneous symptoms of affected children and prevent symptoms in children identified by newborn screening or treated since birth. We have determined thirteen novel mutations in children with the disorder. Two nonsense mutations, eight single missense mutations, three allelic double missense mutations, and two are polymorphisms were identified in the biotinidase gene (BTD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
2
15
1
1
Order By: Relevance
“…Thus, the incidence found in the current study was higher than that observed worldwide and in many countries. Nevertheless, pilot newborn screening Wolf et al (2005) studies in isolated regions or selected groups have disclosed higher incidences (1:4,500 to 1:14,000) than that reported in the present research (Thodi et al 2013;Dunkel et al 1989;Lawler et al 1992;Sarafoglou et al 2009). In Brazil, the available prevalence rates are divergent.…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, the incidence found in the current study was higher than that observed worldwide and in many countries. Nevertheless, pilot newborn screening Wolf et al (2005) studies in isolated regions or selected groups have disclosed higher incidences (1:4,500 to 1:14,000) than that reported in the present research (Thodi et al 2013;Dunkel et al 1989;Lawler et al 1992;Sarafoglou et al 2009). In Brazil, the available prevalence rates are divergent.…”
Section: Discussioncontrasting
confidence: 72%
“…Bis 2001 wurden über 61 Mutationen in 3 von 4 Exons des Biotinidasegens beschrieben [18]. Bis heute sind noch viele weitere neue Mutationen hinzugekommen [43]. Biotin ist ein wichtiges Koenzym, das in der Glukoneogenese, im Stoffwechsel von verzweigtkettigen Aminosäuren und bei der Fettsäuresynthese eine wichtige Rolle einnimmt.…”
Section: Biotinidasemangelunclassified
“…Although biotinidase mRNA and protein are expressed throughout the brain, they are most abundant in centers of the auditory and visual activity, including dorsal and ventral cochlear nuclei, superior olivary complex, and vestibular nucleus (34). Because these areas also seem to contain more biotin than other regions of the brain, it is possible that regulation of the biotin cycle may be of particular relevance for these cells (26,35). We suggest that biotinidase deficiency in combination with limited amounts of biotin may lead to the development of a secondary HCS deficiency that may compromise the survival of cells with a higher metabolic demand such as neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Biotinidase exons were amplified from genomic DNA as previously described (26,27) and subcloned also in pGEM. Both cDNA and exons were sequenced at Laragen (Los Angeles, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation